157k views
3 votes
Help please and thanks :)

Help please and thanks :)-example-1
User Lortschi
by
4.5k points

2 Answers

6 votes

Answer:

Your answer is - 11/3

Explanation:

Hope this helps!

User Bathyscapher
by
4.6k points
4 votes

Answer:

-
(11)/(3)

Explanation:

Using the rules of exponents


(1)/(a^(m) )
a^(-m)


(a^(m)) ^(n) =
a^(mn)

Consider the right side


((1)/(27)) ^(a+3)

=
((1)/(3^3)) ^(a+3)

=
(3^(-3)) ^(a+3)

=
3^((-3a-9))

Now we have

9 =
3^((-3a-9)) , that is

3² =
3^((-3a-9))

Since the bases on both sides are equal, equate the exponents

- 3a - 9 = 2 ( add 9 to both sides )

- 3a = 11 ( divide both sides by - 3 )

a = -
(11)/(3)

User Dylan Parry
by
5.2k points